Considerations for Newborn Screening for Critical Congenital Heart Disease in Low- and Middle-Income Countries - Bistra Zheleva; Sreehari M. Nair; Adriana Dobrzycka; Annamarie Saarinen (MDPI AG, 2020)
We propose several considerations for implementation of critical congenital heart disease (CCHD) screening for low- and middle-income countries to assess health system readiness for countries that may not have all the downstream capacity needed for treatment of CCHD. The recommendations include: (1) assessment of secondary and tertiary level CHD health services, (2) assessment of birth delivery center processes and staff training needs, (3) data collection on implementation and quality surgical outcomes, (4) budgetary consideration, and (5) consideration of the CCHD screening service as part of the overall patient care continuum.